Generalized projection algorithms for maximal monotone operators and relatively non expansive mappings in Banach spaces - Klin-Eam C. (2014)
In this paper, we prove strong convergence theorems of modified Halpern's iteration for finding a common element of the zero point set of a maximal monotone operator and the fixed point set of a relatively nonexpansive mapping in a Banach space by using two hybrid methods. Using these results, we obtain new convergence results for resolvents of maximal monotone operators and relatively nonexpansive mappings in Banach spaces.